How endothelial cell metabolism shapes blood–brain barrier integrity in neurodegeneration - Wang, Jiaxin; Chen, Yuchun; Chen, Shiteng; Mu, Zihan; Chen, Jun (Frontiers in Molecular Neuroscience, 2025)
Background/objectiveEndothelial cells, a monolayer of cells adjacent to blood vessels, play a critical role in maintaining vascular function through metabolic pathways such as glycolysis, fatty acid, and amino acid metabolism. Recent studies have revealed their significant involvement in neurodegenerative diseases, although the underlying mechanisms remain unclear.MethodsBy reviewing literature from the past decade, we summarized the metabolic alterations and functional changes of endothelial cells in neurological disorders.ResultsIn neurodegenerative diseases such as stroke, Alzheimer’s disease, multiple sclerosis, and aging, metabolic dysregulation in cerebral vascular endothelial cells disrupts their normal function and is closely associated with blood–brain barrier impairment.ConclusionAberrant endothelial cell metabolism compromises the integrity of the blood–brain barrier and exacerbates the pathological progression of neurodegenerative diseases. Our review further explores the therapeutic potential of targeting endothelial cell metabolism in various pathological contexts, aiming to provide novel insights for the prevention and treatment of related disorders.